Fine mapping and functional validation of the maize nicosulfuron-resistance gene CYP81A9 - Zhang, Yongzhong; Zhang, Qingrong; Liu, Qingzhi; Zhao, Yan; Xu, Wei; Hong, Cuiping; Xu, Changli; Qi, Xiushan; Qi, Xinli; Liu, Baoshen (Frontiers in Plant Science, 2024)
Nicosulfuron, a widely utilized herbicide, is detrimental to some maize varieties due to their sensitivity. Developing tolerant varieties with resistance genes is an economical and effective way to alleviate phytotoxicity. In this study, map-based cloning revealed that the maize resistance gene to nicosulfuron is Zm00001eb214410 (CYP81A9), which encodes a cytochrome P450 monooxygenase. qRT- PCR results showed that CYP81A9 expression in the susceptible line JS188 was significantly reduced compared to the resistant line B73 during 0-192 hours following 80 mg/L nicosulfuron spraying. Meanwhile, a CYP81A9 overexpression line exhibited normal growth under a 20-fold nicosulfuron concentration (1600 mg/L), while the transgenic acceptor background material Zong31 did not survive. Correspondingly, silencing CYP81A9 through CRISPR/Cas9 mutagenesis and premature transcription termination mutant EMS4-06e182 resulted in the loss of nicosulfuron resistance in maize. Acetolactate Synthase (ALS), the target enzyme of nicosulfuron, exhibited significantly reduced activity in the roots, stems, and leaves of susceptible maize post-nicosulfuron spraying. The CYP81A9 expression in the susceptible material was positively correlated with ALS activity in vivo. Therefore, this study identified CYP81A9 as the key gene regulating nicosulfuron resistance in maize and discovered three distinct haplotypes of CYP81A9, thereby laying a solid foundation for further exploration of the underlying resistance mechanisms.